Eficacia de enraizadores bajo dos sistemas de propagación para la clonación de genotipos de alta productividad de café robusta (Coffea canephora), en Babahoyo, provincia de Los Ríos - Velásquez Mora, Vanessa Valentina (2017)
VIII. SUMMARY The present experimental work was carried out in the lands of the Hacienda "La Clementina" or currently called Cooproclem located at km 23.8 of the Babahoyo - La Unión road, with coordinates Latitude: 1º 42'50,60¨ and length: 79º 21' 11,15 and 37 msnm, according to the Holdribge classification, the area has a humid tropical climate, with an annual average temperature of 31.1 ° C, precipitation of 1549.8 mm / year, relative humidity of 82% and 968 hours of heliofanía Of annual average. The objective of the research was to evaluate the effectiveness of rooting in the process of cloning of robust coffee (Coffea canephora) under two propagation systems. The following rooting plants were used: Hormonagro 1, Fertisa Kelp, Iber Mar E-15, Flormona and Prodigio nitro; Aloe crystals were used as organic agent. The propagation systems consisted of three rooting beds which had a dimension of 2.0 x 0.50 m, were filled with fine sand possessed arches and transparent plastic that formed a tunnel that completely covered the beds; The other spread system was substrate-filled (sand, earth and organic matter), these were separated into three blocks of 175 sheaths and each group had the seven treatments each treatment had 25 sheaths, in total there were 525 sheaths with substrate. With the use of rooting, no statistical differences were observed in the variables under study compared to the control. According to the Robusta coffee propagation system, statistical differences were observed in the survival variables cuttings and health status; Where the system of sleeves proved to be superior to that of rooting chamber. As for the variable costs in the treatments under study, it is indicated that the treatments witnessed a cost of 406.9 USD (covers) and 429.4 USD (camera). Also, it is indicated that the treatment Witness chamber recorded the best net benefit with USD